Pengujian Black Box pada Aplikasi E-Commerce OpenCart dengan Metode Equivalence Partitioning dan Boundary Value Analysis - Fairus In'am Pratama; Eka Mira Novita Subroto; Radina Mutia Haira; Muhammad Ainul Yaqin (Department of Science and Technology Ibrahimy University, 2023)
E-commerce applications have become a significant trend in modern trade. One popular open-source e-commerce application is OpenCart. Testing the application is paramount to ensure that OpenCart functions appropriately and meets the required quality and performance. This study aims to conduct Black Box testing on the OpenCart e-commerce platform using the Equivalence Partitioning (EP) and Boundary Value Analysis (BVA) methods. The testing is carried out to ensure the application's functionality directly relates to user satisfaction and trust. EP divides input data into partitions based on valid and invalid values, while BVA tests input values based on specific boundaries. The focus of the testing is on the checkout feature, which is an essential component of any e-commerce application. The testing flow follows the Software Testing Life Cycle (STLC) approach. The test results show a 57.14% level of conformity using EP and 100% using BVA. Based on these two results, the overall conformity level is 78.57%. The testing results indicate that the system performs well within the tested boundary values but may require improvements in the combination of partition usage.STLC (Software Testing Life Cycle). Hasil pengujian menunjukkan tingkat kesesuaian sebanyak 57,14% pada EP dan 100% pada BVA. Berdasarkan dua hasil tersebut, didapatkan tingkat kesesuaian sebesar 78,57%. Hasil pengujian menunjukkan jika sistem dapat berjalan dengan baik pada nilai-nilai batasan yang diuji, tetapi masih perlu perbaikan pada kombinasi penggunaan antara partisi.